Choosing differently? College application behaviour and the persistence of educational advantage - Judith Delaney; Paul J. Devereux (The Economic and Social Research Institute (ESRI), 2020)
We use administrative data from Ireland to study differences in college application behaviour between students from disadvantaged versus advantaged high schools. Ireland provides an interesting laboratory for this analysis as applicants provide a preference-ordering of college programs (majors) and marginal applications are costless. Also, college admission depends almost completely on grades in the terminal high school examinations. Thus, we can compare the application choices of students who have equal chances of admission to college programs. Conditional on achievement and college opportunities, we find that students from advantaged high schools are more likely to apply to universities and to more selective college programs. They are also more likely to have preferences that cluster by program selectivity rather than by field of study. Our results suggest that, alongside differences in achievement, differences in college application behaviour also cause persons from advantaged high schools to be more likely to enrol in selective colleges and enter more selective programs. Importantly, we find that enrollment gaps for equally qualified applicants are smaller than differences in application behaviour; the relatively meritocratic centralized admissions system based on achievement undoes much of the effect of the differences in application behaviour.
Keywords: 330; Hochschule; Schulauswahl; Studierende; Weiterführende Schule; Dienstleistungsqualität; Irland